The Relationship between Sitting Positions When Doing a Zoom Meeting with Sleepiness - Nazhim, Muhammad; Eko Poerwanto (Junior Medical Journal, 2023)
The Directorate of Learning and Student Affairs, Directorate General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia has issued a Guide to Organizing Odd Semester 2020/2021 Learning in Higher Education stating that students and universities use a communication tool in the form of distance learning (PJJ). However, distance learning using zoom has an impact on concentration and causes several back complaints accompanied by excessive sleepiness. This study used an analytical method with a cross sectional approach, and the sample selection used a simple random sampling technique. The number of samples used is 70 respondents. Data collection was carried out using a questionnaire. Data were analyzed by Pearson correlation test. There is a significant positive correlation between sitting position and sleepiness in YARSI FK students during a zoom meeting with an r value of 0.499 and a p value of 0.001 and the equation of the line y=3.2124x – 0.7257